Reference Values for Healthy Swallowing Across the Range From Thin to Extremely Thick Liquids - Steele CM; Peladeau-Pigeon M; Barbon CAE; Guida BT; Namasivayam-MacDonald AM; Nascimento WV; Smaoui S; Tapson MS; Valenzano TJ; Waito AA; Wolkin TS (American Speech Language Hearing Association, 2019)
Purpose Thickened liquids are frequently used as an intervention for dysphagia, but gaps persist in our understanding of variations in swallowing behavior based on incremental thickening of liquids. The goal of this study was to establish reference values for measures of bolus flow and swallowing physiology in healthy adults across the continuum from thin to extremely thick liquids. Method A sex-balanced sample of 38 healthy adults underwent videofluoroscopy and swallowed 20% weight-to-volume concentration barium prepared in thin and slightly, mildly, moderately, and extremely thick consistencies using a xanthan gum thickener. Participants took comfortable sips and swallowed without a cue; sip volume was measured based on presip and postsip cup weights. A standard operating procedure (the ASPEKT method: Analysis of Swallowing Physiology: Events, Kinematics and Timing) was used to analyze videofluoroscopy recordings. Results The results clarify that, for thin liquid sips (10–14 ml), a single swallow without clearing swallows is typical and is characterized by complete laryngeal vestibule closure, complete pharyngeal constriction, and minimal postswallow residue. Aspiration was not seen, and penetration was extremely rare. Bolus position at swallow onset was variable, extending as low as the pyriform sinuses in 37% of cases. With thicker liquids, no changes in event sequencing, laryngeal vestibule closure, pharyngeal constriction, or postswallow residue were seen. The odds of penetration were significantly reduced. A longer timing interval until onset of the hyoid burst movement was seen, with an associated higher bolus position at swallow onset. Other timing measures remained unaffected by changes in bolus consistency. Conclusion The results include new reference data for swallowing in healthy adults across the range from thin to extremely thick liquids.
Keywords: Adult; Barium Sulfate; Contrast Media; Deglutition; Female; Food Additives; Humans; Male; Middle Aged; Polysaccharides, Bacterial; Reference Values; Young Adult